Implementation of Pastoral Supervision as an Effort to Improve the Duties and Role of Pastors in Pastoring and Teaching - Delima Anria Maena Banjarnahor; Andar Gunawan Pasaribu (Tinta Emas Institute, 2025)
Pastoral care and teaching represent the two central pillars of a pastor's calling, forming the theological and practical foundation of congregational spiritual life. In the context of the Pentecostal Church in Indonesia (Gereja Pantekosta di Indonesia – GPdI), these responsibilities are carried out within an autonomous church structure, allowing each local congregation to define its own vision and ministry strategy. However, this autonomy presents challenges, particularly the absence of a standardized and structured supervisory system. The situation is further complicated by the economic realities faced by many pastors, who often serve bi-vocationally, and the diversity in educational and denominational backgrounds among them. This study explores the implementation of pastoral supervision within local GPdI churches and its impact on the effectiveness of pastors in their roles. Using a qualitative descriptive approach, data were gathered through literature review, document analysis, and interviews with active pastors, including those from non-GPdI backgrounds. The findings indicate that pastoral supervision is mostly informal, relational, and lacks structural support, often occurring only in response to crises. The study highlights the need for a holistic, context-sensitive supervisory model that emphasizes mentoring, theological enrichment, and cross-regional support. Such a model is essential for equipping GPdI pastors to serve effectively as shepherds and teachers amid contemporary ministry challenges.